5 must have Google Chrome extensions for educators / Siti Zaharah Mohd Ruslan - Mohd Ruslan, Siti Zaharah (FSKM Universiti Teknologi MARA (UiTM) Cawangan Negeri Sembilan, 2021)
Have you used Google products while teaching online? Are you looking for new ways to involve students when the semester begins? Do you want to make your life a lot easier for yourself? Even though you just responded YES to one of these questions, Chrome extensions are individualised software programmes that customise your Google experience to match your needs. Essentially, Chrome extensions are like little digital hacks that make an educator's life more tolerable, especially during distancing learning.